Pendidikan Pesantren dan Transformasi di Era Digital Sebuah Tinjauan Filosofis dan Pedagogis - Saimin Saimin; Siti Mahmudah Noorhayati (TSAQOFAH, 2026)
Although digital transformation in pesantren education has been discussed in various studies, studies that comprehensively integrate philosophical and pedagogical dimensions remain limited. This study aims to analyze the philosophical foundations, challenges, and direction of pesantren education transformation in the digital era. This study used a qualitative approach with a literature study design. Data were obtained through documentation of books, journal articles, regulations, and relevant scholarly sources on pesantren education, Islamic educational philosophy, digital literacy, and pedagogical transformation. The data were analyzed using content analysis and thematic analysis through the stages of identification, classification, interpretation, and synthesis. The results show that the transformation of pesantren education includes strengthening ontological, epistemological, and axiological foundations; integrating the turats curriculum with technology; changing the roles of kiai and santri; developing digital literacy; and implementing contextual and hybrid learning. This study produces a transformation framework that connects tauhid, adab, an integrative knowledge system, and digital competence. The conclusion of this study affirms that technology needs to be positioned as an educational tool guided by Islamic values, rather than as the primary goal of pesantren transformation. The implications of this study include the importance of strengthening educator competence, digital ethics, data security, and technology-based learning governance so that the transformation of pesantren education remains relevant, adaptive, and rooted in the identity of Islamic scholarship.